2021
DOI: 10.3390/en14030530
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Integration of the Traditional Architectural Element Mashrabiya into the Ventilation Strategy for Buildings in Hot Climates

Abstract: This paper reviewed related research works and developments on the traditional architectural element “mashrabiya” focusing on its history, design and structure, typology, and functions in hot climates. Moreover, the paper assessed the effect of the traditional mashrabiya on the indoor thermal environment and thermal comfort in a selected case study building. For this purpose, two similar rooms were investigated in a selected historic building with abundant mashrabiyas located in the Makkah Region, specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Bagasi et al [172] presented a review work on the mashrabiya, describing its functions, history, design, structure and typology, mainly in hot weather zones. Mashrabiya is a natural forced ventilation device, frequently used in the traditional architecture of Arab countries.…”
Section: Energy Saving and Emission Reductionmentioning
confidence: 99%
“…Bagasi et al [172] presented a review work on the mashrabiya, describing its functions, history, design, structure and typology, mainly in hot weather zones. Mashrabiya is a natural forced ventilation device, frequently used in the traditional architecture of Arab countries.…”
Section: Energy Saving and Emission Reductionmentioning
confidence: 99%
“…With the emergence of advanced designing tools such as parametric modelling, Luigi Giovannini's work developing the shape variable Mashrabiya (SVM) has risen to prominence [3] in the field of Mashrabiya studies. Similarly, Bagasi and Calautit [4] and Bagasi et al [5], have conducted numerous comprehensive studies on Mashrabiya as a passive cooling technique.…”
Section: Relevant Workmentioning
confidence: 99%
“…Nabawi believes that Najdi art has achieved environmental sustainability because it uses local materials from the surrounding environment, and the dyes are made from local plants [26]. A study conducted by Bagasi et al found that Mashrabiya played an active role in Hijaz architecture, as they contributed to regulating internal temperatures by increasing air flow inside and reducing relative humidity [23]. At a broader level, Al-Ban saw that the Hijazi urban fabric considered ventilation, natural light, and the formation of shadows through the heights of dwellings and their proximity to or distance from each other [29].…”
Section: Environmental Valuesmentioning
confidence: 99%